Characteristics of commercial oriented strand boards (OSB) present on the market - Jakimovska popovska, Violeta; Iliev, Borche (Faculty of design and technologies of furniture and interior-Skopje, 2020)
The paper analyzes the properties of oriented strand boards (OSB) present on the market in our country. In the past years there has been an increased interest for construction of wooden buildings, where the wood-based panels are one of the basic materials for structural and non-structural use. In such buildings different types of OSB can be used as load-bearing members or as general purpose boards, as well as in dry or humid conditions, depending on the place of incorporation in the building. It is important to take an overview of the characteristics of these panels that are present on the market in our country, which will contribute to better understanding of the proper use of OSB according to their physical and mechanical properties. Commercially produced OSB panels taken from one company from wood-based panel market were tested. Evaluation of the quality of the panels was made on the basis of the results obtained for the physical and mechanical properties of the panels. Properties of OSB panels were tested according to the national MKС standards and European norms. Tested OSB panels taken from the market are not fully in accordance with the technical specifications given by the manufacturer of these boards, and the requirements of the standards for OSB panels for use as structural load-bearing panels. There are some deviations found in the quality of the panels in different panels’ direction regarding the values obtained for some of the properties tested.
Keywords: wood-based panels, oriented strand boards (OSB), physical properties, mechanical properties, construction